Antenatal thymus volumes in fetuses that delivered <32 weeks' gestation: An MRI pilot study. (24th September 2020) - Story, Lisa; Zhang, Tong; Uus, Alena; Hutter, Jana; Egloff, Alexia; Gibbons, Deena; Ho, Alison; Al‐Adnani, Mudher; Knight, Caroline L.; Theodoulou, Iakovos; Deprez, Maria; Seed, Paul T.; et al.
Abstract: Introduction: Infection and inflammation have been implicated in the etiology and subsequent morbidity associated with preterm birth. At present, there are no tests to assess for fetal compartment infection. The thymus, a gland integral in the fetal immune system, has been shown to involute in animal models of antenatal infection, but its response in human fetuses has not been studied. This study aims: (a) to generate magnetic resonance imaging (MRI) ‐derived fetal thymus volumes standardized for fetal weight; (b) to compare standardized thymus volumes from fetuses that delivered before 32 weeks of gestation with fetuses that subsequently deliver at term; (c) to assess thymus size as a predictor of preterm birth; and (d) to correlate the presence of chorioamnionitis and funisitis at delivery with thymic volumes in utero in fetuses that subsequently deliver preterm. Material and methods: Women at high‐risk of preterm birth at 20‐32 weeks of gestation were recruited. A control group was obtained from existing data sets acquired as part of three research studies. A fetal MRI was performed on a 1.5T or 3T MRI scanner: T2 weighted images were obtained of the entire uterine content and specifically the fetal thorax. A slice‐to‐volume registration method was used for reconstruction of three‐dimensional images of the thorax. Thymus segmentations were performed manually. Body volumes were calculated by manual segmentation and thymus:body volume ratios were generated. Comparison of groups was performed using multiple regression analysis. Normal ranges were created for thymus volume and thymus:body volume ratios using the control data. Receiver operating curves (ROC) curves were generated for thymus:body volume ratio and gestation‐adjusted thymus volume centiles as predictors of preterm birth. Placental histology was analyzed where available from pregnancies that delivered very preterm and the presence of chorioamnionitis/funisitis was noted. Results: Normative ranges were created for thymus volume, and thymus volume was standardized for fetal size from fetuses that subsequently delivered at term, but were imaged at 20‐32 weeks of gestation. Image data sets from 16 women that delivered <32 weeks of gestation (ten with ruptured membranes and six with intact membranes) and 80 control women that delivered >37 weeks were included. Mean gestation at MRI of the study group was 28 +4 weeks (SD 3.2) and for the control group was 25 +5 weeks (SD 2.4). Both absolute fetal thymus volumes and thymus:body volume ratios were smaller in fetuses that delivered preterm ( P < .001). Of the 16 fetuses that delivered preterm, 13 had placental histology, 11 had chorioamnionitis, and 9 had funisitis. The strongest predictors of prematurity were the thymus volume Z‐score and thymus:body volume ratio Z‐score (ROC areas 0.915 and 0.870, respectively). Conclusions: We have produced MRI‐derived normal ranges for fetal thymus and thymus:body volume ratios between 20 and 32 weeks of gestation. Fetuses that deliver very preterm had reduced thymus volumes when standardized for fetal size. A reduced thymus volume was also a predictor of spontaneous preterm delivery. Thymus volume may be a suitable marker of the fetal inflammatory response, although further work is needed to assess this, increasing the sample size to correlate the extent of chorioamnionitis with thymus size.